Development of asymmetric polyethersulfone (PES) membrane for O/N Separation by using difference technique of membrane formation - Mardhiana, Ismail (2010)
Asymmetric polyethersulfone membrane for gas separation by varying the step of membrane formation have been successfully developed. The casting solution contained of polyethersulfone (PES) as polymer, 1-methyl-2-pyrrolidone (NMP) was employed as a solvent while distilled water (H2O) was used as nonsolvent additives (NSA). Firstly, the casting solution with the concentration of 32.62 wt% PES, 60.58 wt% NMP and 6.8 wt% H2O were used to produce polyethersulfone flat sheet asymmetric membrane. Then, the casting solution was cast on the glass plate by using a casting block with constant thickness which is 400 μm at room temperature (≈25 ºC and average relative humidity is 65%) with difference way of phase inversion which are dry/wet phase inversion, dry at room temperature and dry in oven at 40ºC. The produced membranes were characterized by pure gas permeation experiments by using permeation test unit and the morphology of the membrane was identified using Scanning Electron Microscopy (SEM). For permeation test, oxygen (O2) and nitrogen (N2) were used as a test gases for both uncoated and coated membranes. For the coated membrane, pressure-normalized flux and selectivity showed a more constant trend with increasing feed pressure compare to uncoated membrane for all method of drying process. Coated membrane exhibited higher selectivity than uncoated membranes due to coating of the skin layer defects. Consequently, the best selectivity was found using the dry/wet phase inversion compared than others. The pressure-normalized flux and O2/N2 selectivity were found 25.39 GPU for O2 and 10.12 GPU for N2 and 2.53 respectively. For the Scanning Electron Microscopy (SEM) result, flat sheet membrane prepared by dry/wet phase inversion show the formation of asymmetric membrane with a thin and dense skin layer supported by a thick porous sublayer compared to other which dry at room temperature and dry in oven at 40C with formation of symmetric membrane with the diameter of the pores is almost constant throughout the cross section of the membrane.flat sheet membrane prepared by dry/wet phase inversion show the a dense skin layer and sublayer with existing of microvoid and macrovoid while flat sheet membrane prepared by dry at room temperature and dry in oven at 40C show the formation of porous layer with small microvoid which look sponge like and existing of porous layer with macrovoid respectively. As a conclusion, dry/wet phase inversion technique has successfully developed asymmetric membranes and can be applied for O2/N2 separation.